Systematic reviews of complementary therapies - an annotated bibliography. Part 3: Homeopathy - Vickers Andrew; Hondras Maria; Linde Klaus; Riet Gerben ter; Melchart Dieter (BMC, 2001)
Abstract Background Complementary therapies are widespread but controversial. We aim to provide a comprehensive collection and a summary of systematic reviews of clinical trials in three major complementary therapies (acupuncture, herbal medicine, homeopathy). This article is dealing with homeopathy. Potentially relevant reviews were searched through the register of the Cochrane Complementary Medicine Field, the Cochrane Library, Medline, and bibliographies of articles and books. To be included articles had to review prospective clinical trials of homeopathy; had to describe review methods explicitly; had to be published; and had to focus on treatment effects. Information on conditions, interventions, methods, results and conclusions was extracted using a pretested form and summarized descriptively. Results Eighteen out of 22 potentially relevant reviews preselected in the screening process met the inclusion criteria. Six reviews addressed the question whether homeopathy is effective across conditions and interventions. The majority of available trials seem to report positive results but the evidence is not convincing. For isopathic nosodes for allergic conditions, oscillococcinum for influenza-like syndromes and galphimia for pollinosis the evidence is promising while in other areas reviewed the results are equivocal. Interpretation Reviews on homeopathy often address general questions. While the evidence is promising for some topics the findings of the available reviews are unlikely to end the controversy on this therapy.